2020
DOI: 10.1016/j.psj.2020.05.056
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reducing dietary calcium in prestarter diets (0–4 D) on growth performance of broiler chickens, tibia characteristics, and calcium and phosphorus concentration in blood

Abstract: During the incubation period, the Ca-to-P weight (mg/mg) ratio in the yolk increases from 0.26 on day 0 to 0.92 on day 17.5 and to 2.9 at hatch. Moreover, the absolute Ca content in the yolk increases by 41%, whereas P content decreases by 87%, from day 0 to the day of hatching. Thus, at hatch and during the first days after hatching, there are high reserves of Ca relative to P in the residual egg yolk, risking hypercalcemia and hypophosphatemia. A growth performance study was conducted to explore the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…For example, the Ca content of the yolk increases by 71% from embryonic d 0 to 17.5 ( Hopcroft et al, 2019 ). Previous authors reported no difference in daily FI or daily gain of broilers fed 0.40, 0.60, or 0.80% total Ca from hatch to d 4 post-hatch, whereas further increases in total dietary Ca significantly decreased daily intake and gain ( Mansilla et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, the Ca content of the yolk increases by 71% from embryonic d 0 to 17.5 ( Hopcroft et al, 2019 ). Previous authors reported no difference in daily FI or daily gain of broilers fed 0.40, 0.60, or 0.80% total Ca from hatch to d 4 post-hatch, whereas further increases in total dietary Ca significantly decreased daily intake and gain ( Mansilla et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
“…Response variables that are the most sensitive to Ca and P concentrations in the diet are bone ash, growth performance, and Ca and P digestibility. Growth rate and efficiency are optimized at concentrations of Ca that are suboptimal for bone mineralization ( Bedford and Rousseau, 2017 ; Lagos et al, 2019 ; Mansilla et al, 2020 ). In the current experiment, there was no effect of graded levels of SID Ca on body weight gain and the linear impact of dietary SID Ca on FCR or the AID of P or Ca suggest the requirement is greater than or less than that tested in the current experiment for these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…They are used for pellet materials that either contain ground crops like sand and dirt or with a high mineral such as cattle feed materials. Greater care should be considered when adjusting the rollers with the shell fitted 16 .…”
Section: Background and Surveymentioning
confidence: 99%
“…Close ends allows the feed material to be trapped on the face of the die. Close end roller shell assist in a greatly die face wear by holding back on the natural characteristics of some of the feed formulations; it works to the grooves of each side of die face [10]. The close-end shells are available in different depths and widths and suits many applications but is generally used with poultry feed manufacturing for a well-conditioned, high-grain rations.…”
Section: Roller Shellsmentioning
confidence: 99%
“…When adjusting the rollers, greater care should be considered with this shell tted. If adjusted too tight towards die face, the surface of the tungsten of shell will cause rapid wear [10].…”
Section: Roller Shellsmentioning
confidence: 99%